2007
DOI: 10.1021/es070102q
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Nitrification and Biotransformation of 17α-Ethinylestradiol

Abstract: Biological treatment processes are probably important for preventing the proliferation of steroidal compounds in the environment, and a growing number of reports suggest that nitrification may play a role in removing these chemicals from wastewater. The link between nitrification and biotransformation of 17alpha-ethinylestradiol (EE2) was investigated using enriched cultures of autotrophic ammonia-oxidizers. Batch experiments showed that ring A of EE2 is the site of electrophilic initiating reactions, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(106 citation statements)
references
References 20 publications
8
95
2
1
Order By: Relevance
“…Figure 2b illustrates a positive linear relationship between ammonia oxidation rate and atenolol biodegradation rate. Such a positive correlation was also reported for 17α-ethinylestradiol [14]. This supported the cometabolic biodegradation of atenolol in the presence of ammonium [12], likely mediated by the enriched nitrifying culture through the non-specific enzyme AMO [10,[38][39][40].…”
Section: Atenolol Biodegradation With Ammonia Oxidationsupporting
confidence: 73%
See 1 more Smart Citation
“…Figure 2b illustrates a positive linear relationship between ammonia oxidation rate and atenolol biodegradation rate. Such a positive correlation was also reported for 17α-ethinylestradiol [14]. This supported the cometabolic biodegradation of atenolol in the presence of ammonium [12], likely mediated by the enriched nitrifying culture through the non-specific enzyme AMO [10,[38][39][40].…”
Section: Atenolol Biodegradation With Ammonia Oxidationsupporting
confidence: 73%
“…Ammonia oxidizing bacteria (AOB) in the nitrifying activated sludge are able to degrade a range of aromatic compounds due to its nonspecific enzyme ammonium monooxygenase (AMO) [10,11], following cometabolism in the obligatory presence of a growth substrate such as ammonium [12]. AMO was capable of oxidizing a broad range of aromatic substrates [10,13], probably due to the mechanism of reaction with oxygenated form of AMO [14]. On the other hand, heterotrophs also showed the ability to degrade some pharmaceuticals (ketoprofen, acetaminophen) following metabolic biodegradation pathways [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Certain bacteria are known to excrete dehydrase (Bloch 1971;Sasakawa et al 1958), but dehydration mediated by N. europaea has not been reported. Yi and Harper (2007) demonstrated hydroxylation of A-ring in the treatment of EE2 using the nitrifying activated sludge, whereas we showed hydration of D-ring of E2 by N. europaea. Since the different microorganisms and estrogens were used, it was plausible the different products were observed.…”
Section: Degradation Pathway Of 17b-estradiolmentioning
confidence: 59%
“…These findings suggest that E2 and EE2 are degraded via E1 and that E3 is also an intermediate of E2 degradation. In another study, hydroxylation of A-ring of EE2 was demonstrated during the treatment using nitrifying activated sludge (Yi and Harper 2007), though whether the hydroxylated EE2 has estrogenic activities is still unknown. Many studies have examined the microbial degradation of the natural and synthetic estrogens as reviewed by Cajthaml et al (2009); however, little detailed information about estrogen degradation pathways is available.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have extensively focused on anaerobic conditions since TBBPA is prone to reductively debromination yielding less brominated bisphenol A (BPA), but further anaerobic biodegradation of BPA was not observed [8−10].Previous studies have shown that the co-metabolic reaction can convert recalcitrant compounds to intermediates via catabolic and anabolic pathways of microorganisms which may be more prone to biodegradation [11].Moreover, TBBPA is long-term exposed to aerobic environments before entering the anaerobic environments, and usually co-exists with other organic contaminants. In this regard, it is crucial to understand what extent the aquatic microorganisms may contribute to the elimination of TBBPA.…”
Section: Introductionmentioning
confidence: 99%